PELAKSANAAN KEEFEKTIFITASAN PEMBERIAN SANKSI POINT DALAM PENEGAKKAN DISIPLIN SEKOLAH DI SMA NEGERI 1 LUBUK SIKAPING - Hetri, Dianti Veniza; Erianjoni, Erianjoni; Melia, Yenni (Pendidikan Sosiologi, 2013)
Discipline is one of the components that determine the educational achievement at school. With the discipline in students are expected to arise conducive atmosphere for teaching and learning in schools. As one of the institutions of formal education, SMA Negeri 1 Lubuk Sikaping has issued a policy relating to rules and regulations. Schools impose sanctions for any violation point made by students in an effort to enforce discipline. The purpose of this study was to describe the cause of the implementation of sanctions effectiveness points in the enforcement of discipline in SMA Negeri 1 Lubuk Sikaping and to explain the impact of the implementation of sanctions effectiveness points in the enforcement of discipline in SMA Negeri 1 Lubuk Sikaping. The study was conducted in February and September. This type of research is a qualitative approach using a case study type. This research sites in SMA Negeri 1 Lubuk Sikaping. This study is only an attempt to make a description, a picture of a situation as it should. Selection of informants using purposive sampling technique. Type of data is the primary data and secondary data were collected through observations, interviews and documentation. Data analysis technique used is an interactive model of analysis. Results of this study indicate that (1) point penalty imposed may restrict students in behaving towards positive. This is due to the strict sanctions and fair in its implementation. (2) good socialization process also makes this point penalty to be more effective. (3) the cooperation of all components of the school such as the principal, vice-principal, subject teachers and counseling teachers make effective sanctions this point. (4) the impact of the adoption of this point of sanctions is to make students more responsible and the teacher can help teachers to control the students behavior.